Respuesta :

Answer:

So we have this equation:

2   (3x-2) - 4x = 5x + 2

You can first operate the parenthesis, knowing that a(b+c) = ab + ac (conmutative)

2(3x-2) - 4x = 5x + 2

2 * 3x - 2 * 2 - 4x = 5x + 2

6x - 4 -4x = 5x + 2

Now, we can operate the x:

6x - 4 -4x = 5x + 2

2x - 4 = 5x + 2

And sum 4 in both sides and substract 5x in both too.

2x - 4 = 5x +2

2x - 4 + 4 - 5x' = 5x + 2 + 4 -5x

Now we can operate:

-3x = 6

And we can divide by -3 the two sides...

x = 6/-3 = -2

ACCESS MORE